Decolonizing Education and the Green Economy: Religious and Indigenous Resistance to Extraction in Indonesia - Sopian Lubis; Husayn Muhyideen Ali; Ali Ali (Elkuator Research and Publication, 2025)
Indigenous communities in Indonesia often face serious challenges, especially when dealing with conflicts related to resistance to epistemic dominance in extractive economic practices. This resistance is manifested through a decolonial educational approach rooted in spiritual and religious values. This research uses a qualitative document analysis method, by examining various academic literature, laws and regulations, and empirical case studies. In this study, the form of resistance of indigenous peoples is not only physical or material, but also includes the dimension of knowledge and perspective on nature and development. This study specifically highlights the case of the Mollo and Orang Rimba communities, as well as the role of two major religious organizations in Indonesia, namely Muhammadiyah and Nahdlatul Ulama. All three are understood as a more grounded alternative to the concept of green economy which tends to be state-centric. The ritual practices of indigenous peoples and religious fatwas are a form of profound criticism of the current direction of development. However, contradictions also arise when religious organizations begin to negotiate with community-oriented state policies. The researchers' findings suggest that the decolonization of education and the enforcement of ecological justice are crucial. Both function as a plural and inclusive epistemological foundation in responding to colonialism that has been rooted in the relationship between indigenous peoples, religions, and the state. Therefore, the active involvement of indigenous peoples and religious organizations that prioritize spiritual values as well as a commitment to ecological sustainability and environmental governance has the potential to realize a transformation towards a more just and sustainable life, within the framework of an ecological human rights that respects the rights of indigenous peoples.